GREEN COMPUTING USING RMIT GREEN ICT FRAMEWORK METHOD (CASE STUDY: STIKOM DINAMIKA JAMBI) - Muhamad Irsan; Johan Budiman; Erick Fernando; Dina Fitria Murad (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This paper presents the application of green computer in STIKOM Jambi dynamics. Green computing is one effective way to reduce the effects of global warning. Educational institutions are one institution that uses largeelectrical energy. To support the global warning program, Bali Stikom began to apply green computing. Thisresearch uses the method of RMIT Green ICT. The result, the application of green computing managed to reducethe burden of electricity costs, reduce operating costs from the data center, and reduce the amount of hardwarerequired. In addition to providing benefits to STIKOM, green ICT also provides environmental benefits. Such asreduction of carbon dioxide emissions, reducing resource consumption, and adhering to prevailing governmentregulations. Keywords: green computing, RMIT, green ICT framework